Waqf Land Dispute Resolution in Indonesia and Malaysia: Legal and Cultural Approaches - Ratih Agustin Wulandari; Raimon Efendi; Neng Vivie Nurfauziah Rukmini (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2025)
Abstract: Dispute resolution in the waqf land context is a matter of particular legal complexity; thus, it requires special attention. This research aims to provide a comparative analysis of waqf land dispute resolution mechanisms in Indonesia and Malaysia, with a focus on the role of local cultural values and Islamic legal norms. The present research employs a normative legal research approach, which involves the identification of legal rules, principles and doctrines to provide a resolution to the legal issues under consideration. The results indicate that the resolution of waqf land disputes in Indonesia and Malaysia uses divergent legal and cultural approaches. Despite the adherence to the Islamic waqf principle, there are discernible discrepancies in the dispute resolution methods, legal structures and cultural influences exhibited by these two nations. The influence of local cultural values on the two nations is evident. Indonesia places significant value on deliberation, cooperation and social sustainability, whereas Malaysia places greater emphasis on negotiation, mediation and economics. This research aims to provide tangible insights into institutional reforms and digital innovations in waqf governance and expand comparative analyses to other Islamic jurisdictions, thereby enriching the global discourse on waqf legal practices and dispute resolution.